SPT20 Regulates the Hog1-MAPK Pathway and Is Involved in Candida albicans Response to Hyperosmotic Stress - Wang, Lianfang; Chen, Ruilan; Weng, Qiuting; Lin, Shaoming; Wang, Huijun; Li, Li; Fuchs, Beth Burgwyn; Tan, Xiaojiang; Mylonakis, Eleftherios (Frontiers in Microbiology, 2020)
Candida albicans is the most common fungal pathogen and relies on the Hog1-MAPK pathway to resist osmotic stress posed by the environment or during host invasions. Here, we investigated the role of SPT20 as part of the osmotic response. Testing a C. albicans spt20Δ/Δ mutant, we found it was sensitive to osmotic stress. Using sequence alignment, we identified the conserved functional domains of CaSpt20. Reconstitution of the Spt20 function in a spt20Δ/CaSPT20 complemented strain found CaSPT20 can suppress the high sensitivity to hyperosmotic stressors, a cell wall stress agent, and antifungal drugs in the Saccharomyces cerevisiae spt20Δ/Δ mutant background. We measured the cellular glycerol accumulation and found it was significantly lower in the C. albicans spt20Δ/Δ mutant strain, compared to the wild type strain SC5314 (P<0.001). This result was also supported by quantitative reverse transcription-PCR, which showed the expression levels of gene contributing to glycerol accumulation were reduced in Caspt20Δ/Δ compared to wild type (GPD2 and TGL1, P<0.001), while ADH7 and AGP2, whose expression can lead to glycerol decrease, were induced when cells were exposed to high osmolarity (ADH7, P<0.001; AGP2, P=0.002). In addition, we tested the transcription levels of Hog1-dependent osmotic stress response genes, which revealed that expression was reduced for SKO1 (P<0.001), ORF19.4370 (P<0.001), ORF19.3661 (P=0.017), and SLP3 (P=0.005), while CAT1 expression was evidently induced (P<0.001) in Caspt20Δ/Δ strain. Moreover, the deletion of CaSPT20 in C. albicans reduced phosphorylation levels of Hog1. These findings suggested that SPT20 is conserved in C. albicans and plays an important role in adapting to osmotic stress through regulating Hog1-MAPK pathway.